Female preferences based on male nutritional chemical traits - Giaquinto, Percilia Cardoso [UNESP]; da Silva Berbert, Claudia Militao [UNESP]; Delicio, Helton Carlos [UNESP] (Springer, 2010)
Selection favors females that attend to reliable information about male genetic quality and fitness. Male nutritional condition can be a significant sign of mate quality since poor nutrition can be related to reduced sperm quality, low sperm quantity, sexually transmitted diseases, and parasites. We tested whether female Nile tilapia, Oreochromis niloticus, preferred the chemical cues of males that were well fed with high-protein diet over those fed with low-protein diet. Females do not only discriminate between males but also show a preference for well-fed males, discriminating between the odors with respect to nutritional state, suggesting that they were responding to a food-specific chemical cue. It is therefore likely that nutritional condition is related to the production of pheromones in males. Our results suggest that information about male nutritional state can be conveyed in chemical cues and that females attend to these cues during mate choice.
Keywords: Mating choice; Nutritional state; Chemical cues; Pheromones; Nile tilapia; Oreochromis niloticus